Handmade batik with tuberose motifs as creative home industry idea - Mega Novita; Febrian Murti Dewanto; Aris Trijaka Harjanta; Bambang Agus Herlambang; Dian Marlina; Desi Purwaningsih; Haryo Kusumo (Universitas Muhammadiyah Magelang, 2023)
Batik tulis is a rich cultural heritage of Indonesia, encompassing traditional values and artistic expressions. However, in some regions, there has been a decline in interest and skills in batik tulis making, along with the threat of plagiarism of local batik motifs. Therefore, efforts are needed to develop creative innovations in batik tulis production and ensure the sustainability of local batik traditions. Desa Doplang faces challenges in enhancing the skills of its residents in creating batik tulis with the motif of Polyanthes Tuberosa L., preserving the authenticity and originality of batik motifs, and improving economic well-being through increased production and sales of batik tulis. The Community Engagement Program (PKM) is designed to address these challenges through intensive mentoring, quality control, and efforts to prevent plagiarism. Through technical and creative training, the residents of Desa Doplang have acquired the skills required to produce batik tulis with the motif of Polyanthes Tuberosa L. Mentoring is provided at every stage of production, including the application of wax, dyeing, and the final boiling process. Feedback and constructive advice are given to improve the quality and authenticity of the batik tulis produced. Quality control measures are implemented to ensure that each batik tulis product meets the established quality standards. Additionally, through socialization and education, awareness regarding the importance of authenticity and originality of batik motifs is heightened. The program utilizes a community development, empowerment, and engagement approach. As a result, the program has successfully enhanced the skills of the residents of Desa Doplang in batik tulis production, increased cultural appreciation, and improved economic well-being through enhanced production and sales of batik tulis. The quality of the batik tulis produced has shown continuous improvement alongside the enhancement of skills. Moreover, the program has successfully preserved the local tradition of batik making and strengthened the position of batik tulis with the motif of Polyanthes Tuberosa L. as the flagship product of Desa Doplang. Another positive impact is the increase in the residents' income through the sale of batik tulis at better prices.